1998
DOI: 10.1002/(sici)1096-9136(199802)15:2<160::aid-dia537>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus and Down's syndrome: prevalence, management and diabetic complications

Abstract: Type 1 insulin‐dependent diabetes mellitus (Type 1 DM) is thought to be more prevalent in individuals with Down's syndrome. To ascertain the local prevalence of Type 1 DM in patients with Down's syndrome in a geographically defined area, the four diabetes clinics in Lothian were surveyed and 13 patients with Down's syndrome and Type 1 DM were identified. Using data from previous epidemiological surveys which determined the prevalence of Down's syndrome in the general population, the prevalence rate of Type 1 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 4 publications
12
96
0
4
Order By: Relevance
“…A Dutch study [8] identified three cases in Down's syndrome children aged 0-9 years (prevalence 0.34%), but did not differentiate between type 1 and type 2 diabetes either. In a Scottish study, based on interviews and a clinical database in a region of Scotland [9], a prevalence rate of diabetes in Down's syndrome of between 1.4 and 10.6% was observed, which is considerably higher than reported elsewhere. The prevalence is based on identification of 13 individuals with Down's syndrome and diabetes, which was compared with previous estimates calculating the presumed numbers of individuals with Down's syndrome in the region.…”
Section: The Number Of Births In Denmark Inmentioning
confidence: 75%
“…A Dutch study [8] identified three cases in Down's syndrome children aged 0-9 years (prevalence 0.34%), but did not differentiate between type 1 and type 2 diabetes either. In a Scottish study, based on interviews and a clinical database in a region of Scotland [9], a prevalence rate of diabetes in Down's syndrome of between 1.4 and 10.6% was observed, which is considerably higher than reported elsewhere. The prevalence is based on identification of 13 individuals with Down's syndrome and diabetes, which was compared with previous estimates calculating the presumed numbers of individuals with Down's syndrome in the region.…”
Section: The Number Of Births In Denmark Inmentioning
confidence: 75%
“…The high association of CD with DS has not yet been clarified, however both, CD and DS patients present more frequent dysfunction in their immune system and are more predisposed to autoimmune diseases, such as thyroid diseases, diabetes mellitus type 1, lupus and arthritis. 4,5,6,12 Besides that, this association may be related to shared common genetic markers. It has been shown that the DS patients with CD present the characteristic CD associated with high-risk human leukocyte antigens (HLA) DR3 and DQ2 alleles.…”
Section: Discussionmentioning
confidence: 98%
“…1 Different studies have shown that patients with DS present several immune dysfunctions, 2,3 which lead to increased frequency of recurrent infections, as well as autoimmune diseases. A high association between DS and autoimmune diseases has been already reported by several authors, [4][5][6] with the most significant association with celiac disease (CD) [7][8][9][10][11] and autoimmune thyroiditis. 12,13 CD affects individuals of all ages and is characterized by permanent gluten intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Se levarmos em conta a prevalência de DC diagnosticada através do EmA positivo, essa prevalência é de 7%. O alto grau de associação de DC com SD ainda não foi totalmente esclarecido, no entanto, os portadores dessas afecções freqüentemente apresentam disfunções imunológicas, ficanco predispostos às doenças autoimunes, tais como doenças da tireóide, diabetes melito tipo 1, lúpus e artrite 4,5,6,12 . Além disso, essa associação pode estar relacionada a marcadores gené-ticos comuns compartilhados.…”
Section: Discussionunclassified
“…Vários estudos já foram publicados relatando alto grau de associação entre SD e doenças autoimunes [4][5][6] , principalmente doença celía-ca (DC) [7][8][9][10][11] e tireoidite autoimune 12,13 .…”
Section: Introductionunclassified